Examining the Problems and Expectations during The Pandemic Process According to Technology Integration Levels of Teachers and Technology Leadership Self-Efficacy of School Administrators - Özçelik, Ali; Özek, Müzeyyen Bulut (My University, 2023)
The aim of this study is to reveal whether the problems and expectations experienced by the education system stakeholders during the pandemic process differ according to the technology integration levels of the teachers and the technology leadership self-efficacy perception levels of the school administrators. The general survey model was used to conduct research. \"Indicators of Technology Integration Scale\" was used to determine the technology integration indicators of teachers, and the \"Technological Leadership Self- Efficacy Scale for School Administrators\" was used to determine the technology leadership self-efficacy of school administrators. In addition, the Distance Education Questionnaire was used to investigate the problems experienced by teachers and school administrators during the pandemic, the changes they expect in terms of educational practices after the pandemic, and the measures that can be taken in possible situations. This study was carried out with a total of 489 people, including 369 teachers and 120 school administrators. Data management and analysis were performed using SPSS statistical program. The results of this investigation show that teachers find themselves at a sufficient level in terms of technology integration and school administrators in terms of technology leadership self-efficacy. Both teachers with high technology integration level and school administrators with high technology leadership self-efficacy perceptions stated that they experienced problems such as lack of experience in developing e-learning content during the pandemic process, the targeted acquisitions are not suitable for online environments, and the inability to provide education according to the individual interests and abilities of students in online distance education. They stated that they expect students to increase their motivation towards school and learning with the return to face-to-face education after the pandemic.
Keywords: Teacher; Pandemic; School administrator; Technology Integration; Technological Leadership